STRATEGI PENGEMBANGAN OBYEK WISATA BATU OJUNG DI DESA LUBUK KARAK KECAMATAN DHARMASRAYA MENGGUNAKAN ANALISIS SWOT: Case Study on Lubuk Karak Village, Dharmasraya District - Mandalia, Siska; Putri; Fadila, Nessa (Jurnal Manajemen Perhotelan dan Pariwisata, 2023)
This study aims to identify the strengths, weaknesses, opportunities, and threats (SWOT) associated with tourism objects and then formulate a comprehensive development strategy. This study used a qualitative approach, utilizing primary and secondary data sources. Primary data was collected through field visits, interviews with local stakeholders, and observations, while secondary data was collected from relevant literature and documents. The findings revealed that Batu Ojung has unique natural and cultural strengths, including a beautiful landscape and traditional heritage. However, challenges such as limited infrastructure, lack of promotion, and environmental concerns were identified as weaknesses. Opportunities include growing interest in ecotourism and cultural experiences, while threats include competition from nearby attractions and potential negative impacts on the local environment. Based on the SWOT analysis, a development strategy is proposed, to capitalize on strengths, the strategy suggests improving infrastructure, promoting the site through various marketing channels, and encouraging community involvement. Overcoming weaknesses involves investing in basic facilities, implementing sustainable practices, and providing training to local communities for hospitality and tourism-related activities.